INDIGENOUS USURY SYSTEM AND INFORMAL MICROFINANCE IN IBADAN, NIGERIA (2017)
Informal microfinance is one of the veritable sources of venture finance in developing countries. While informal microfinance such as rotating savings and credit associations, and cooperative associations have received significant scholarly attention,limited research has been conductedon the features that sustain Indigenous Usury System (IUS) in Nigeria. The IUS provides informal credit to small scale businesses and low income earners at prohibitively high interest ratesthat have attracted negative and exploitative perceptions of the system. The study, therefore,examined the features (relevance, accessibility, usage, network, repayment schedule and sanctions) that have sustained contemporary IUS in Ibadan, Nigeria. Rational choice theory guided the study while exploratory research design was adopted. Ibadan city was selected as the study area because of the preponderance of IUS. The study population was indigenous usury lenders and lendees. Usury lenders were identified through snowballing. Five Key Informant Interviews (KIIs), 10 In-depth Interviews (IDIs) and two case studies were conducted with usury lenders. Usury lendees were categorised into trader-lendees and formal worker lendees. The trader-lendees were purposively identified from three most popular modern markets in Ibadan - Gbagi, Bodija and Agbeni. Formal worker-lendees comprised formal sector workers (civil servants, teachers and bank workers). Twenty and 30 IDIswere conducted with formal sector lendees and trader-lendees respectively. Five KIIs and two case studies were carried out with trader-lendees. Eight Focus Group Discussions comprising four sessions each for traders-lendees and formal worker-lendees were also conducted. Data were content analysed. The relevance of IUS in contemporary informal microfinance was predicated on the subjective, but contextual rational interpretation of the system as benevolence (aanu). The IUS readily met the financial needs of lendees, which they considered inaccessible in formal finance institutions. Contextual negative impressions of potential default and possible coercive sanctions by lenders inadvertently sustained the IUS. Access to IUS fund was dependent on referral from a trusted guarantor (trader-lendee), reputation of a lendee’s organisation (formal sector workers) and good credit history. Usury lenders financed both economic (trading and contract finance) and social (burial ceremonies, children education, health and international migration expenses) ventures. Financing depended on the rational evaluation of the venture vis-à-vis the likelihood of loan repayment. Lenders assisted trader-lendees through business advice, customer reference and patronage. Repayment interest rates ranging from 5.0% to 10.0% were charged on the monthly principal balance outstanding, thus resulting in an exploitative aggregate annual interest rate of 60.0% and 120.0% respectively. Repayment default attracted sanctions such as police arrest, incarceration, property seizure, blacklisting, social stigmatisation and physical assault. Despite associated high interest rates and punitive coercion, lendees tended to place more premium on the timeliness and availability of the loan when needed. Informal usury system remained a major source of finance for lendees despite itsexploitative nature due toits accessibility which gives it an interpretation of contextualised magnanimity